COVID-19 and vaccination induced changes in hospital activity in Malta, Q1 2020 to Q1 2021: a population-based study - Sarah Cuschieri; David Borg; Steve Agius; Hagen Scherb; Victor Grech (SpringerOpen, 2022)
Abstract Background COVID-19 has severely impacted global healthcare services. Malta has only one acute state hospital, Mater Dei Hospital (MDH), and at the time of writing is the most vaccinated country in Europe. Malta thus provides an ideal setting to assess the impact of COVID-19 on healthcare services at population level, including the impact of vaccination on hospital admissions. Methods Hospital data was obtained as anonymised totals from MDH's Clinical Performance Unit and the European Centre for Disease Prevention and Control. COVID-19-related data was obtained from the Ministry of Health dashboard. Comparative assessments were performed to explore associations between the COVID-19 situation, vaccination, and hospital activity. Poisson regression was used to model the counts of monthly accident and emergency (A&E), outpatient clinics attendances and hospital admissions. Results A&E, hospital admissions, and outpatient clinics attendances declined (31.88%; 23.89%; 29.57%; p < 0.01 respectively) with onset of COVID-19 till April 2021 when compared to pre-COVID years (2017-2019). Admissions due to COVID-19 initially increased in parallel to the population's COVID positivity. Vaccination rollout led to a decline in COVID-19 admissions. Conclusions The drastic drop in admissions and outpatient attendees was expected but not for A&E attendees as acutely ill patients should still have attended. This is of public health concern since delayed or deferred medical management increases population morbidity, mortality and increases the eventual burden on the healthcare system. Mass vaccination saw the return to normality with an increase in A&E burden.